Study of the Beginning Stage of Crystallization of Numeral Concept (International Journal of Scientific Research in Science and Technology, 2025)
In this paper, we have tried our best to make attempts to study of beginning stage of the crystallization of numeral concept.
Keywords: Ancient Mathematics; Vedic Mathematics; Cube root; Number Theory; Hindu Mathematics